PENERAPAN INFORMATION TECHNOLOGY ETHICS DALAM PROSES BELAJAR MAHASISWA - Herlawati Herlawati (Universitas Bina Sarana Informatika, 2010)
Many research on Information Technology (IT) Ethics for ethical guidance when students graduate or the technical delivery (asinkron or direct course). But in reality, sometimes we found confused students when implement IT ethic as a result of inconsistent thins when they learn. Ethics of copyright, for example, is the contrast in the library on campus copying without permission of books (most of the overseas issue). Or some professors who share module copyright campus when teaching at other colleges. Although the meaning of